INDONESIA'S SOFT POWER IN TURKEY THROUGH DANCE ARTS: EFFORTS TO STRENGTHEN BILATERAL RELATIONS (2021-2025) - Nanat, Achmad Maulana; Agfajrina Cindra Pamungkas; Try Danuwijaya (UIN Alauddin Makassar, 2026)
This study aims to analyze Indonesia's cultural diplomacy strategy through traditional dance in strengthening bilateral relations with Türkiye during the 2021–2025 period. The research employs a qualitative descriptive approach using secondary data collected from academic literature, official government documents, journal articles and other relevant publications. The analysis is grounded in Joseph Nye's Soft Power theory and the Multi-Track Diplomacy framework developed by Louise Diamond and John W. McDonald to examine the contributions of both state and non-state actors in Indonesia's cultural diplomacy. The findings demonstrate that traditional dance functions as an effective instrument of soft power by enhancing Indonesia's national image, fostering mutual understanding and strengthening diplomatic, economic, educational and socio-cultural cooperation between Indonesia and Türkiye. Cultural activities organized by the Indonesian Embassy, the Indonesian diaspora, universities, cultural communities and media platforms created sustainable people-to-people engagement and broadened Indonesia's cultural presence in Türkiye. The synergy among government institutions, business actors, educational institutions, diaspora communities and the media significantly contributed to the effectiveness of cultural diplomacy. This study concludes that traditional dance has become a strategic component of Indonesia's foreign policy and recommends strengthening multi-stakeholder collaboration to further enhance bilateral relations with Türkiye through cultural diplomacy.